Corporate Crime and Efforts To Overcome It - Ismaidar Ismaidar; T. Riza Zarzani; Lindawati Br Surbakti (International Journal of Law, Crime and Justice, 2024)
Corporate Crime or what can be called a criminal act of corruption is a crime committed jointly where the impact can damage democracy, morality, harm state finances, violate the social and economic rights of the community. Nowadays, corporate development seems to be increasingly rapid both in terms of quality, quantity and in the field of business it operates. Corporations operate in fields such as banking, transportation, entertainment, agriculture and so on. The existence of corporations brings many benefits to society and the state, such as: an increase in state treasury income from taxes and foreign exchange, opening up job opportunities, increasing technology transfer and so on. However, there are also negative impacts from these corporations, such as: environmental pollution, exploitation or depletion of natural resources, tax manipulation, exploitation of workers and so on. The emergence of this negative impact is due to corporations pursuing large profits.